Kandungan Klorofil Dan Pertumbuhan Semai Kakao (Theobroma cacao L.) Pada Perlakuan Cekaman Kekeringan Yang Berbeda - Prihastanti, Erma - (Bioma : Berkala Ilmiah Biologi, 2010)
Drought stress will result in decreasing the rate of water absorption by plant roots. This decrease will result indisturbances in plant growth, especially in a growing network includes the addition of Growth in dry mass, volume,length or area of cells resulting from the interaction of processes in plants through photosynthesis, respiration,transport, water relations and nutrient balance. Morphological and physiological responses of plants against stressand patterns of plant adaptation to different environments is very important especially for the purposes of cultivationand the prediction of the properties of responsive plant tersebut. Purpose of this research is to examine changes incontent klorofil a and b, and growth (number of leaves and plant height ) cocoa seedling age of 12 months atdifferent water stress.The study was conducted in the village of Plana Banyumas, Central Java Province, which lasted from January2007 to June 2008. Cacao tree used was 12 months in which the cocoa beans used for seeding of hybrid clonesderived from cocoa pods from the village of O, o Kulawi Donggala District of Central Sulawesi. Cocoa seedlingswere given three treatments of water stress that soil water content 75%, 50% and 25%. Observations of variablechlorophyll a and b,number of leaves and plant height after one month and two months of stress.The results showed drought effect on leaf chlorophyll content of seedlings of cocoa, where the plants grown on soilwater content of 50% have chlorophyll a and b are lower than those grown on soil water content 75%. The growth ofcocoa seedlings are best when planted with soil water content 75%, because the soil moisture content of 50% and25% of the number of leaves and plant height decreased